Perancangan Wi-Fi Corner Hotspot Menggunakan Mikrotik Di Tempat Umum - Risman Hidayat; Dahliyusmanto Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The development of internet technology is currently overgrowing, so the need for technological tools is increasing, one of which is the need for the internet. One easy way and much-loved by people is to use a wireless system/hotspot system. However, in using Wi-Fi network services in aplace with a limited bandwidth/speed, the user becomes wasteful both in terms of time and internet network usage. The purpose of this research is to design a Wi-Fi corner hotspot system using a proxy in a public place at the Otot IT store and make the voucher system key access to the internet network. This research was carried out in the Otot IT shop environment on JalanRaya Pekanbaru-Bangkinang KM43, Koto Tibun village. The stages carried out in this study began with problem identification, literature study, identification of system requirements, system design, and system testing. The RB 941-2nD (hAP Lite) router will be the primary device in creating a Wi-Fi corner hotspot. The voucher system is made using the Mikhmon application.Testing the internet connection quality can be seen using the PING, download, andupload parameters. In this study, the data analysis technique used is qualitative analysis with the Quality of Service (QoS) method. This study shows that users who want to use internet service access must have a voucher first, different from before where users only ask for a Wi-Fi password and can repeatedly enter with the same password. If you do not have a voucher, youcan directly come to the store admin to buy it. With the voucher system, the network quality in the store will be able to be controlled and managed, such as limiting the sale of vouchers if users are using the internet a lot and avoiding repeated logins by users as before doing the voucher systemKeyword: Wi-Fi Corner, Hotspot, Mikrotik, Otot IT, & Voucher